Systematic Biopsy of the Prostate can Be Omitted in Men with PI-RADS™ 5 and Prostate Specific Antigen Density Greater than 15%. Issue 2 (5th August 2021) - Tafuri, Alessandro; Iwata, Atsuko; Shakir, Aliasger; Iwata, Tsuyoshi; Gupta, Chhavi; Sali, Akash; Sugano, Dordaneh; Mahdi, Abtahi Seyed; Cacciamani, Giovanni E.; Kaneko, Masatomo; Cai, Jie; Ukimura, Osamu; et al.
Abstract : Purpose: We evaluated the prostate cancer and clinically significant prostate cancer detection on systematic biopsy (SB), target biopsy (TB) alone and combined SB and TB in men with Prostate Imaging Reporting and Data System™ (PI-RADS™) 5 lesion. Materials and Methods: From a prospectively maintained prostate biopsy database, we identified consecutive patients with PI-RADS 5 lesion on multiparametric magnetic resonance imaging. The patients underwent multiparametric magnetic resonance imaging followed by transrectal TB of PI-RADS 5 lesion and 12-core SB. The prostate cancer and clinically significant prostate cancer (Grade Group, GG ≥2) detection on SB, TB and SB+TB were determined for all men and accordingly to prostate specific antigen density. Statistic significant was set a p <0.05. Results: Overall, 112 patients met inclusion criteria. The detection rate of prostate cancer for SB, TB and SB+TB was 89%, 93% and 95%, respectively, and for clinically significant prostate cancer it was 72%, 81% and 85%, respectively. SB added 2% prostate cancer and 4% clinically significant prostate cancer detection to TB. A total of 78 patients had prostate specific antigen density >0.15 ng/ml 2, and the detection rate of PCa for SB, TB and SB+TB was 92%, 97% and 97%, respectively, and for clinically significant prostate cancer it was 79%, 91% and 95%, respectively. In this population, if SB was omitted, 0 prostate cancer and only 4% (3) of clinically significant prostate cancer would be missed. The clinically significant prostate cancer detection rate improved with increased prostate specific antigen density for SB (p=0.01), TB (p <0.0001) and combined SB+TB (p=0.002). Conclusions: In patients with PI-RADS 5 on multiparametric magnetic resonance imaging and prostate specific antigen density >0.15 ng/ml 2, SB marginally increases clinically significant prostate cancer detection, but not overall prostate cancer detection in comparison to TB alone. Systematic biopsy did not affect patients' management and can be omitted on this population.